El riesgo financiero del F.C. Barcelona al adquirir a Dembelé,en el periodo 2017-2020 (2020)
Soccer is increasingly linked to finances, because, in addition to being a sport, it involves movements of money, income, costs, expenses, etc. Soccer clubs, to finance their activities, benefit from issues such as public entry to stadiums, sale of shirts, image rights or publicity. However, they incur enormous expenses, for example, in the acquisition of players, that is, their main asset, thus creating problems to solve this investment. The objective of this study is to determine the financial risk involved in buying Ousmane Dembelé, which has a high price in the market. That said, the research guiding question is the following: How much does signing Dembelé represent a financial risk for F.C. Barcelona, during 2017-2020? Which is answered through the use of two very common tools in the field of statistics and finance: The Ordinary Least Squares (M.C.O) method and the Value at Risk (VaR). The most significant results show that as the number of player injuries is reduced by 1%, the player's market value increases by € 1,100,000, and as the player's salary increases, his market value increases by € 1,280,000. By performing the VaR, the club loses € 14,849,741 when Dembelé is fit to play and € 15,356,533 when he can’t play.